Comparative Analysis Regarding Gen’z Satisfaction Over Mobile Network Connectivity Between Jio and Airtel In Ahmadabad City - Modi, Krish; Bokhiriya, Anjali; Vidani, Jignesh (PT FORMOSA CENDEKIA GLOBAL, 2024)
This Paper Makes a Comparison In Terms Of The Level Of Satisfaction Of Generation Z In Ahmedabad Based On Mobile Network Connectivity Between Jio And Airtel. It Gathers Significant Insights By Bringing Up A Discussion About Various Dimensions Of The Consumer Experience, Which Mainly Include Overall Satisfaction, Network Reliability, Data Speed, And Responsiveness Of The Customer Service, Into Appropriate And Deeper Connections With Age. The Results Shown That The Young Customers First And Foremost Care About The Network's Performance And Adequate Service Support. Regarding Value For Money, It Was Determined That Generation Z Values Overall Value, In Other Words, High-Quality Services At Low Price. Practical Implications And Discussion With Mobile Network Providers The Several Implications That Are Practical For Mobile Network Providers Concern Reaching Strategic Marketing, Improving The Quality Of The Services, And Then Adding Value To The Offering. Conclusion: Recommendation For Future Studies: Therefore, From The Results, There Is A Need To Analyse Larger Demographics Longitudinally And Look At The Impacts Of Technological Innovations On Consumer Satisfaction. From This Perspective, On A Whole, This Study Gives Meaning To The Understanding Of Consumer behaviour Within The Telecommunication Industry, Which Thus Again Reiterated The Call For Change By Service Providers According To Changing Preferences Of Younger Consumers.